Misteri Cinta Tersembunyi: Analisa Tarjuman Al-Asywaq Dan Fusus Al-Hikam Karya Ibn ‘arabi - Miswari, Miswari (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Lhokseumawe, 2018)
This article aims to analyze the ideas of Wahdatul Wujud which were developed by Ibn ‘Arabi in his works. The author analyzes two works of Ibn ‘Arabi namely Fusus Al-Hikam and Tarjuman Al-Asywaq. The two works are full of symbolic language. The author tries to describe the views in the two works with a simple narrative and tries to find relevant references to explain the teachings. The author finds that in Fusus Al-Hikam, the analogies used are very simple, but the systematization is very complicated. While in and Tarjuman Al-Ashwaq, the analogy is also simple and even seems